The effect of high-intensity intermittent and moderate-intensity continuous exercises on neurobiological markers and cognitive performance - Yusuf Buzdagli; Murat Ozan; Nurcan Baygutalp; Furkan Oget; Raci Karayigit; Neslihan Yuce; Emirhan Kan; Fatih Baygutalp; Halil Ucar; Yusuf Buzdağlı (BMC, 2024)
Abstract Background The effects of exercise on cognitive functions and general brain health have been increasingly studied. Such studies conducted among athletes are very important to understanding the effects of different exercise methods on biochemical parameters and cognitive performance. The present study aimed to compare the neuroprotective effects of high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) based on biochemical parameters and cognitive performance in athletes. Methods A total of twenty-eight elite male boxing athletes aged > 18 years, with at least eight years of training experience, who successfully achieved national and international levels were included in this study. The elite athletes participating in the study were aged 24.43 ± 4.72 years, 14.45 ± 5.89 years of training experience, had a body weight of 74.64 ± 7.82 kg, and had a height of 177 ± 7.15 cm. Athletes who consumed any stimulants during the testing or supplementation phase, nutritional supplements, or steroids that may have affected hormone levels or sports performance in the last three months were excluded from this study. Venous blood samples were obtained, and cognitive performance tests (Stroop tests) were applied (i) immediately after high-intensity intermittent exercise (HIIE), (ii) one hour after HIIE, (iii) immediately after moderate-intensity continuous exercise (MICE), and (iv) one hour after MICE. Serum BDNF, S100B, and NSE levels were measured after each session. Results Serum BDNF levels were significantly (F = 2.142, P < 0.001, ηp 2 = 0.589) greater in the HIIE group (5.65 ± 1.79 ng/mL) than in the control group (1.24 ± 0.54 ng/mL) and MICE group (3.38 ± 1.29 ng/mL) for the samples obtained immediately after exercise. Serum S100B levels were significantly (F = 3.427, P < 0.001, ηp 2 = 0.427) greater in the HIIE group (71.92 ± 23.05 ng/L) than in the control group (47.39 ± 15.78 ng/L), however there was no significant difference between the HIIE and MICE groups (59.62 ± 28.90 ng/L) in the samples obtained immediately after exercise. Serum NSE levels were significantly (F = 1.475, P < 0.001, ηp 2 = 0.312) greater in the HIIE group (14.57 ± 2.52 ng/mL) than in the control group (9.51 ± 3.44 ng/ML mL), however there was no significant difference between the HIIE and MICE groups (59.62 ± 28.90 ng/L) in the samples obtained immediately after exercise. Compared with control groups, both HIIE and MICE improved cognitive performance demonstrated by the Stroop test results. Again, HIIE was superior to MICE in terms of Stroop task reaction time and error rate (incongruent task) scores. Conclusion HIIE and MICE have favorable effects on improving cognitive performance and neuroprotection in an athlete population. HIIE is considered to be superior to MICE in improving neuroprotection and cognitive performance. Our study has remarkable results demonstrating the benefits of HIIT on neuroprotection and cognitive performance. HIIE is recommended instead of MICE, especially in sports where cognitive performance is more important.